2020
DOI: 10.1080/10298436.2020.1859506
|View full text |Cite
|
Sign up to set email alerts
|

A progressive hedging approach for large-scale pavement maintenance scheduling under uncertainty

Abstract: This study approaches a multi-stage stochastic mixed-integer programming model for the highlevel complexity of large-scale pavement maintenance scheduling problems. The substance of some parameters in the mentioned problems is uncertain. Ignoring the uncertainty of these parameters in the pavement maintenance scheduling problems may lead to suboptimal solutions and unstable pavement conditions. In this study, annual budget and pavement deterioration rate are considered uncertainty parameters. On the other hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…This process can be related to the exponential trend of pavement deterioration. That is, the pavement deterioration follows an exponential trend, and IRI is increased exponentially ( 44 ). Further, pavement age, ESAL, and SN are the most influential parameters on IRI, which indicates the importance of traffic and structural conditions on pavement roughness.…”
Section: Resultsmentioning
confidence: 99%
“…This process can be related to the exponential trend of pavement deterioration. That is, the pavement deterioration follows an exponential trend, and IRI is increased exponentially ( 44 ). Further, pavement age, ESAL, and SN are the most influential parameters on IRI, which indicates the importance of traffic and structural conditions on pavement roughness.…”
Section: Resultsmentioning
confidence: 99%
“…Fani et al [98] proposed a stochastic model, considering annual budget and pavement deterioration rate as uncertain pavement factors. They found that the complexity of the model increased as the number of network sections and scenarios increased.…”
Section: Flexible Pavement Costmentioning
confidence: 99%
“…Li & Zhang, 2021) (Ta et al, 2020). Ignoring this uncertainty can lead to suboptimal decisions or unreliable solutions (de Jonge et al, 2015) (Fani et al, 2022) (de la Barra et al, 2020). To address this challenge, the concept of distributionally robust optimization (DRO) has emerged as a powerful framework that explicitly considers a range of possible distributions or  Robust learning and optimization in distributionally robust stochastic variational inequalities under uncertainty (Hengki Tamando Sihotang, et al) uncertainty sets(S. Lu et al, 2020) (Siqin et al, 2022) (Gu et al, 2021)(C. Shang & You, 2018) (Ning & You, 2019) (Miao et al, 2021).…”
Section: Introductionmentioning
confidence: 99%